2021
DOI: 10.3390/ijerph182212008
|View full text |Cite
|
Sign up to set email alerts
|

Basketball-Specific Small-Sided Games Training during Ramadan Intermitting Fasting: Do Changes in Body Composition, Sleep Habits, and Perceived Exertion Affect Technical Performance?

Abstract: The objective of this study was to assess the effects of an additional small-sided games (SSGs) training program during Ramadan intermitting fasting (RIF) on technical performance depending on changes in body composition, sleep habits, and ratings of perceived exertion (RPE). Twenty-four professional male basketball players from the Tunisian first division participated in this study. The players were randomly assigned to an intervention group (INT; n = 12) or an active control group (CON; n = 12). Both groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Apart from affecting performance, the daily caloric quantity intake was suggested as a factor contributing to decreased performance during fasting by some studies [16,17]. In contrast, several studies revealed no significant differences in this parameter during the RIF month compared to before Ramadan [5,18]. Meal time, however, has recently been shown to affect energy balance [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from affecting performance, the daily caloric quantity intake was suggested as a factor contributing to decreased performance during fasting by some studies [16,17]. In contrast, several studies revealed no significant differences in this parameter during the RIF month compared to before Ramadan [5,18]. Meal time, however, has recently been shown to affect energy balance [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of an additional SSGs training program were assessed during RF on technical performance depending on changes in body composition, sleep habits, and RPEs. 62 Twenty-four professional male basketball players from the Tunisian first division participated in this study. The players were randomly assigned to an intervention group ( n = 12) or an active control group (CG, n = 12).…”
Section: Highlights Of the Year's Literaturementioning
confidence: 99%
“…The studies comprised 922 participants of both sexes (190 female, 554 male, and 178 not specified in the study). Participants ranged from 8-year-old beginners (Martínez-Fernández et al, 2015) to senior players at the professional level (Boros et al, 2020;Brini et al, 2021). The game format manipulations ranged from 1 vs. 1 (Clemente et al, 2021b;Clemente et al, 2019;Clemente et al, 2020b;González-Espinosa et al, 2021) to 5 vs. 5 (Clemente et al, 2021b;Clemente et al, 2017;Clemente et al, 2019;Clemente et al, 2020b;Ferioli et al, 2020;Figueira et al, 2022;Köklu et al, 2017;Mateus et al, 2019;McCornick et al, 2012;Piñar et al, 2009;Práxedes et al, 2021;Tallir et al, 2012).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Results indicated that the SSGs group outperformed the HIIT group in technical skills, with significant differences observed in dribbling and shooting control. Similarly, Delextrat & Martinez (2014) Brini et al (2021) analyzed the effect of SGGs during the Ramadan period (intermittent fasting) and observed a reduction in individual technical performance. Furthermore, a study analyzed the increase in technological elements (FITLIGHT) combined with SSGs, revealing improvements in passing, shooting, and dribbling skills among young players following a 10-week intervention (Hassan et al, 2023).…”
Section: Tactical-technical Behaviormentioning
confidence: 99%